Laboratory Biomarkers and Immunological Modulation of Sintilimab in Gastric Cancer: A Meta-Analysis Focused on Tumor Markers and T-Cell Subsets: Sintilimab for Gastric Cancer: Efficacy, Markers, and Safety - Zhang, Xian; Zhao, Qiang; Tang, Huafei; Qin, Rui; Tian, Ting; Li, Congying; Ma, Rui (Journal of Medical Biochemistry, 2025)
Background: Sintilimab, a PD-1 inhibitor, has emerged as a promising immunotherapeutic agent in gastric cancer. However, its impact on laboratory-based biochemical markers and immune indicators remains underexplored. This meta-analysis aimed to evaluate the changes in tumor biomarkers and T lymphocyte subsets, alongside clinical outcomes, in patients receiving sintilimab.Methods: A comprehensive literature search of randomized controlled trials (2022–2025) was conducted across CNKI, Wanfang, VIP, and PubMed databases. Primary outcomes included serum tumor markers (CEA, CA199, CA242) and immune parameters (CD4⁺, CD8⁺ T-cell subsets). Secondary outcomes were ORR, DCR, OS, PFS, and adverse reactions. RevMan 5.2 was used for meta-analysis.Results: Sixteen studies were included. Sintilimab treatment significantly reduced CEA, CA199, and CA242 levels (P < 0.0001), and favorably modulated immune subsets by increasing CD4⁺ and decreasing CD8⁺ cell counts. These biochemical and immunological improvements correlated with higher ORR, DCR, and OS, without increased adverse events (P > 0.05).Conclusion: Sintilimab confers measurable improvements in key laboratory-based tumor and immune biomarkers, supporting its utility in clinical biochemical monitoring and immunotherapy response evaluation for gastric cancer patients. These findings align with the emerging integration of immunotherapy and biochemical diagnostics in oncology.
Keywords: Sintilimab; Gastric cancer; CEA; CA199; CA242; CD4⁺; CD8⁺; Biochemical markers; Laboratory diagnostics; Meta-analysis